Design and development of solar energy system for use in isolated home in Singapore - Ang, Hui Ru (2009)
Renewable energy has been a research area of exponentially increasing interest since the past decade along with the more attention that people pay to environment and energy problems. The growing demand for clean sources of energy has expanded dramatically in recent years as conventional energy like oil becomes scarce and more expensive. Because of this growth, it has lead to demand for searching alternative source energy. Therefore, the aim of this project is to build a solar energy system in an isolated home.